Transgenic mouse models of lipoprotein metabolism and atherosclerosis. - Breslow, J L (1993)
Lipoprotein transport genes have either been added to the germ line of mice by transgenic techniques or knocked out by homologous recombination in embryonic stem cells. The resultant over- or underexpression of these genes has resulted in new insights about how these genes function in the body and their role in lipoprotein metabolism. Either singly or in combination, these genetic modifications can be used to engineer the mouse to make it a better model for human lipoprotein disorders and atherosclerosis.